Possible Lithosphere-Atmosphere-Ionosphere Coupling effects prior to the 2018 Mw = 7.5 Indonesia earthquake from seismic, atmospheric and ionospheric data. (February 2020) - Marchetti, Dedalo; De Santis, Angelo; Shen, Xuhui; Campuzano, Saioa A.; Perrone, Loredana; Piscini, Alessandro; Di Giovambattista, Rita; Jin, Shuanggen; Ippolito, Alessandro; Cianchini, Gianfranco; Cesaroni, Claudio; Sabbagh, Dario; et al.
Graphical abstract: Highlights: Seismic acceleration is detected for 2 months before the mainshock occurrence. An increase of atmospheric anomalies is found 3.7 months before the mainshock. An increase of ionospheric anomalies occurred about 2.7 months before the mainshock. A simultaneous anomaly is detected both in atmosphere and ionosphere on 2018-08-02. Nigh-time ionospheric electron density increase on 2018-08-19 as possible precursor. Abstract: In this study, we analyse Lithosphere Atmosphere Ionosphere Coupling (LAIC) effects to identify some phenomena that could, possibly, be linked to the preparation phase of the MW  = 7.5 earthquake occurred in Indonesia on September 28th, 2018, by investigating the eight months preceding the seismic event. First, we find a seismic acceleration that started two months before the mainshock. Then, studying some physical properties of the atmosphere (skin temperature, total column water vapor and aerosol optical thickness), we find two increases of atmospheric anomalies about 6 and 3.7 months before the mainshock, and the latter one is very promising as a candidate for seismic-related phenomena. Furthermore, we investigate ionospheric disturbances, by analysing the Swarm and, for the first time, China Seismo-Electromagnetic Satellite (CSES), magnetic and electron density data during quiet geomagnetic time. From different techniques, we find interesting anomalies concentrated around 2.7 months before the mainshock. On August 19th, 2018, Swarm and CSES showed an enhancement of the electron density during night time. We critically discuss the possibility that such phenomenon can be a possible pre-seismic-induced ionospheric effect. Finally, we performed a cumulative analysis using all detected anomalies, as a test case for a possible chain of physical phenomena that could happen before the earthquake occurrence. With this study, we support the usefulness to collect and store large Earth ground and satellite observational dataset that in the future could be useful to monitor in real time the seismic zones to anticipate earthquakes, although nowadays, there is no evidence about useful prediction capabilities.